Effect of tamoxifen on the coronary vascular reactivity of spontaneously hypertensive female rats - Borgo,M.V. (2011)
Tamoxifen has been associated with a reduction in the incidence of myocardial infarction. However, the effects of tamoxifen on coronary reactivity have not been fully elucidated. The objective of this study was to determine the effects of chronic treatment with tamoxifen on coronary vascular reactivity in spontaneously hypertensive rats (SHR). Female SHR were divided into four groups (N = 7 each): sham-operated (SHAM), sham-operated and treated with tamoxifen (10 mg/kg) by gavage for 90 days (TAMOX), ovariectomized (OVX), and ovariectomized and treated with tamoxifen (OVX+TAMOX). Mean arterial pressure (MAP), heart rate (HR), coronary perfusion pressure (CPP), and coronary vascular reactivity were measured. MAP and HR were reduced (9.42 and 11.67%, respectively) in the OVX+TAMOX group compared to the OVX group (P < 0.01). The coronary vascular reactivity of the OVX+TAMOX group presented smaller vasoconstrictor responses to acetylcholine (2-64 µg) when compared to the OVX group (P < 0.01) and this response was similar to that of the SHAM group. The adenosine-induced vasodilator response was greater in the TAMOX group compared to the SHAM and OVX groups (P < 0.05). Baseline CPP was higher in OVX+TAMOX and TAMOX groups (136 ± 3.6 and 130 ± 1.5 mmHg) than in OVX and SHAM groups (96 ± 2 and 119 ± 2.3 mmHg; P < 0.01). Tamoxifen, when combined with OVX, attenuated the vasoconstriction induced by acetylcholine and increased the adenosine-induced vasodilatory response, as well as reducing the MAP, suggesting beneficial effects of tamoxifen therapy on coronary vascular reactivity after menopause.